ESTIMATION OF PRIMARY PRODUCTIVITY FOR TUNA IN INDIAN OCEAN - Ende Kasma; Takahiro Osawa; I Wayan Sandi Adnyana (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science))
Indonesia has abundant fisheries potency, one of fisheries potency in Indian Ocean is tuna fish. Primary productivity data used as indicator of tuna fisheries potency in Idian Ocean.Research location is in Indian Ocean 070 - 210 S and 1070 - 1210 E. Weekly satellite data in 2007 used are chlorophyl, sea surface temperature, Photosynthetic Available Radiation (PAR) and euphotic zone (Zeu) data. Daily fisheries data is from tuna fish catching data 2007 in PT. Perikanan Samudera Besar (PT. PSB). Satellite data is processed by Vertically Generalized Production Model (VGPM) formula to obtained primary productivity. Tuna fish catching data correlated to satellite data to know correlation of primary productivity value to fish catching data.Result of this research is there four species of tuna fish catch in Indian Ocean, that are Madidihang or Yellowfin tuna (Thunnus albacores), Bigeye tuna (Thunnus obesus), Southtern Bluefin tuna (Thunnus macoyii), and Albacore (Thunnus alalunga). Where 73% tuna fish is Bigeye tuna. Bigeye, Albacore and Yellowfin tuna are produced annually, while Southern Bluefin tuna in northwest monsoon is no fish production. Chlorophyll-a, sea surface temperature and primary productivity value in research location are from 0,06 mg/m3 to 0,38 mg/m3, from 24,640C to 31,820C, and from 73,22mgC/m2 to 658,57 mgC/m2 respectively. Coefficient correlation in primary productivity and fish catching in fishing ground area is small (r = 0.008), its explained that, fish catching number is not influenced by primary productivity. In high or low primary productivity condition tuna fish catched in Indian Ocean area. Potential fishing ground area of Bigeye tuna, Albacore, Yellowfin and Southern Bluefin tuna in Indian Ocean are in 110 – 160 S and 1060 – 1210 E, the primary productivity value is from 73 mgC/m2day to 732 mgC/m2day and differences of sea surface temperature value of tuna fish are from 240 C to 310 C, 240 C to 300 C, and 250 C to 310 C for Bigeye tuna, Albacore and Yellowfin tuna, respectively. While Southern Bluefin tuna distribution is in temperature area from 260 C to 300 C and primary productivity value is from 92 mgC/m2day to 449 mgC/m2day